2009
DOI: 10.1373/clinchem.2008.112805
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: Novel Biomarkers for Human Cancer

Abstract: BACKGROUND: MicroRNAs (miRNAs), small RNA molecules of approximately 22 nucleotides, have been shown to be up-or downregulated in specific cell types and disease states. These molecules have become recognized as one of the major regulatory gatekeepers of coding genes in the human genome.CONTENT: We review the structure, nomenclature, mechanism of action, technologies used for miRNA detection, and associations of miRNAs with human cancer. miRNAs are produced in a tissue-specific manner, and changes in miRNA wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
337
1
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(349 citation statements)
references
References 73 publications
5
337
1
5
Order By: Relevance
“…This sequence-specific binding leads to target mRNA degradation or repression of its translation, consequently decreasing encoded protein levels (Lee et al, 1993;Bagga et al, 2005). In fact, miRNAs have already been implicated as regulators of many physiological and pathological processes, including development, proliferation, differentiation, apoptosis, and tumor progression and metastasis (Bartel et al, 2004;He et al, 2004;Esquela-Kerscher et al, 2006;Negrini et al, 2008;Tavazoie et al, 2008;Bartels et al, 2009;Garzon et al, 2009). However, the role of miRNAs in cervical cancer metastasis and the precise mechanism of its action in these tumor types remain largely unexplored.…”
Section: Characterization Of the Microrna Expression Profile Of Cervimentioning
confidence: 99%
“…This sequence-specific binding leads to target mRNA degradation or repression of its translation, consequently decreasing encoded protein levels (Lee et al, 1993;Bagga et al, 2005). In fact, miRNAs have already been implicated as regulators of many physiological and pathological processes, including development, proliferation, differentiation, apoptosis, and tumor progression and metastasis (Bartel et al, 2004;He et al, 2004;Esquela-Kerscher et al, 2006;Negrini et al, 2008;Tavazoie et al, 2008;Bartels et al, 2009;Garzon et al, 2009). However, the role of miRNAs in cervical cancer metastasis and the precise mechanism of its action in these tumor types remain largely unexplored.…”
Section: Characterization Of the Microrna Expression Profile Of Cervimentioning
confidence: 99%
“…The use of miRNA as biomarkers of brain injury in the serum or CSF could serve as tools for both diagnosing and stratifying TBI severity. As a biomarker of pathologic process, miRNA have several unique features, including cell-, tissue-, and disease-specific expression patterns [192,193]. Studies of CSF in a rat model of mild blast TBI found a significant increase in levels of one miRNA, miR-let-7i, as early as 3 hours post injury [194].…”
Section: Micrornasmentioning
confidence: 99%
“…In addition, miRNA expression profiling of tumors in digestive organs has been identified through signatures associated with diagnosis, staging, progression, prognosis and response to treatment (Schetter et al, 2008;Bartels et al, 2009;Wang et al, 2009).…”
Section: Effects Of Multiple-target Anti-microrna Antisense Oligodeoxmentioning
confidence: 99%